High-heat-shielding flash spinning sheet
By using the mixing of loaded magnesium oxide hybrid materials and polyethylene in the flash spinning process, combining hot pressing and winding processes, the problem of insufficient thermal shading performance of flash products is solved, and high thermal shading performance and low shading are achieved The flash spinned sheet with thermal attenuation rate expands the depth of application.
Patent Information
- Application Number
- CN202310866664.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-14
AI Technical Summary
Existing flash products lack thermal shading performance adjustment, which cannot meet the market's demand for high thermal shading performance, limiting the application depth of flash shading materials.
A hybrid material loaded with magnesium oxide is mixed with polyethylene to prepare high heat-hide flash spinning sheets through flash spinning process, combining hot pressing and winding processes to improve heat-hide performance and reduce the heat-hide rate attenuation rate.
It significantly improves the heat proof performance and heat proof attenuation rate of flash spinning sheets, expands the application range of flash evaporation materials, and extends the service life.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flash steaming production, and in particular relates to a flash spinning sheet with high heat shielding. Background Art
[0002] Flash spinning refers to a spinning method in which a polymer solution is extruded at a high pressure above the boiling point of its solvent, and the solvent flashes, causing the polymer to cool and solidify to form fibers. It is also called solution flash spinning. It requires that the polymer and the solvent do not decompose above the boiling point of the solvent, and the solvent evaporates easily. The extruded solution stream causes the solvent to flash when the pressure suddenly decreases, causing the polymer to solidify into fibers. The most prominent feature of flash spinning technology is phase separation. For example, during the dissolution process, the polymer and the solvent are stirred at high temperature and high pressure to be converted into a homogeneous solution; in the low-pressure chamber, the pressure is slightly reduced to cause the solution to undergo a certain degree of phase separation, forming a two-phase solution, one of which is a polymer-rich phase and the other is a solvent-rich phase; finally, when the solution enters the air at room temperature and pressure from the spinneret, the solvent is converted into steam and quickly separated from the polymer.
[0003] US Patent Publication No. 8,048,513 relates to flash spun plexifilamentary fiber bundles having a surface area of less than 10 m2 / g and a crush value of at least 1 mm / g.
[0004] Chinese Patent Publication No. CN114622341A The present invention relates to a polyethylene non-woven fabric and its application, characterized in that the raw material of the polyethylene non-woven fabric is mainly polyethylene, the first average bending stiffness DG of the polyethylene non-woven fabric is 28-240 mN•cm, and the ratio of DG / XG is 1.03-3.0, and the larger average bending stiffness test value in the same sample is defined as the first average bending stiffness DG, and the smaller test value is defined as the second average bending stiffness XG. The polyethylene non-woven fabric of the present application has certain bending stiffness and good air permeability.
[0005] European patent EP1264013B1 relates to a method for flash spinning a web of plexifilamentary film-fibril strands of a synthetic fiber-forming polymer and laying the web to form a nonwoven batting material, comprising the steps of: spinning a spinning fluid consisting essentially of a synthetic fiber-forming polymer and a spinning agent, flash spinning the spinning fluid into a spinning unit maintained at a lower pressure at a pressure greater than the autogenous pressure of the spinning fluid to form a web of plexifilamentary film-fibril strands of a synthetic fiber-forming polymer, applying an electrostatic charge to the web by passing the web through a corona and laying the web on a grounded surface to form a mat of plexifilamentary film-fibrils suitable for consolidation into a sheet.
[0006] Chinese patent publication number CN114687069A relates to a multifunctional polymer nonwoven fabric and fabric thereof, characterized in that the attenuation rate of its elongation at break ▲E is 0.20-0.50; ▲E=1 E2 / E1; E1 is the elongation at break of the multifunctional polymer nonwoven fabric not subjected to aging test; E2 is the elongation at break of the multifunctional polymer nonwoven fabric subjected to aging test; the value of E2 is less than 0.5. The process of the present application is simple and widely used.
[0007] Chinese patent publication number CN114687068A relates to an improved flash-steamed nonwoven fabric. The present invention aims to solve the problem that the brightness of flash-steamed nonwoven fabrics in the prior art decreases after being used for a period of time, and provides an improved flash-steamed nonwoven fabric. The loss rate ▲F of the D65 fluorescence brightness of the improved flash-steamed nonwoven fabric is 0.20-0.30; wherein ▲F=1 F2 / F1; F1 is the D65 fluorescence brightness of the nonwoven fabric that has not been aged; F2 is the D65 fluorescence brightness of the nonwoven fabric after aging; the process conditions of the aging treatment are: the irradiance in the wavelength range of 300-400 nanometers is 60±2w / m2, the black mark temperature is 65±2℃, the air temperature of the test chamber is 38±3℃, the relative humidity is 50±10%, and the drying time is 1440 hours. The flash-steamed nonwoven fabric of the present invention can maintain a high brightness after being used for a period of time.
[0008] European patent EP2264230A3 relates to a fiber nonwoven sheet having a longitudinal uniformity index of less than about 82 (g / m2)1 / 2, an elongation at break greater than about 15%, and a ratio of tensile strength to basis weight greater than about 0.78 N / cm / g / m2, wherein the sheet comprises plexifilamentary membrane fibril material and can be prepared by a rotary process.
[0009] Chinese patent publication number CN114908478A relates to a light and thin flash-evaporated polymer non-woven fabric, whose wet tensile strength retention rate is 0.70-0.85, the front smoothness is 180-250 seconds, and the gram weight is 35-45g / m2; the invention is prepared by a flash evaporation process, and the raw material is polyethylene; the light and thin flash-evaporated polymer non-woven fabric of the present application has good toughness and softness, and at the same time has a good wet tensile strength retention rate, which is beneficial to prolonging its service life.
[0010] Japanese patent JP4565005 relates to a method of flash spinning a nonwoven fibrous sheet from a polymer solution containing about 12% to about 33% by weight of filler particles. The filler is preferably insoluble in the polymer. The resulting plexifilamentary film-fibril sheet has increased air permeability without losing any liquid barrier properties.
[0011] Chinese patent publication number CN114990712A relates to a flash-steamed fabric and its application, which has a wet transverse tensile strength of 1600-1900 N / m after soaking in deionized water at 40°C, a wet longitudinal tensile strength of 2800-3100 N / m after soaking in deionized water at 40°C, a dynamic friction coefficient of 0.1-0.25, and a gram weight of 35-45 g / m2. This application can be used in the field of medical protection, various protective clothing, etc.
[0012] European patent EP1213374 relates to improved flash spun plexifilamentary film fibril sheets for fluid microfiltration and aseptic packaging. The above and other characteristics of the present invention are achieved by a sheet suitable for liquid microfiltration, the sheet having a permeability that results in a pressure drop of less than 4 psid at a flow rate of 10 gal / hr, and having an efficiency of filtering 99% of 1 to 2 micron sized dust particles at a pressure differential of 30 psid. The present invention also relates to a sheet suitable for aseptic packaging, having a Gurley Hill porosity of less than 15 seconds and a spore log reduction value of at least 2.5.
[0013] However, there is no relevant research on how to adjust the heat-shielding performance of flash steam products in the prior art, while the demand for heat-shielding flash steam products in the market is objectively existing. Therefore, how to improve the heat-shielding performance of flash steam products to expand the application depth of flash steam materials has become a technical problem that needs to be urgently solved in this field. Summary of the invention
[0014] The object of the present invention is to provide a flash-spun sheet with high heat shielding properties in view of the above problems.
[0015] In order to achieve the above object, the present invention adopts the following technical solutions: A high heat shielding flash spun sheet, the raw material of the flash spun sheet includes polyethylene, and the thickness of the flash spun sheet is 0.1 mm to 0.5 mm; The heat shielding rate of flash-spun sheets is 15% to 30%; Heat shielding rate test: measured according to the national standard GB / T 41560-2022.
[0016] The thickness of the flash-spun sheet is 0.15 mm to 0.3 mm.
[0017] The grammage of the flash spun sheet is greater than 30 g / m2.
[0018] The flash spun sheet has a grammage of less than 120 g / m2.
[0019] The flash spun sheet has a grammage of less than 100 g / m2.
[0020] The flash spun sheet has a grammage of less than 90 g / m2.
[0021] The heat shielding rate of flash-spun sheets is 15% to 20%.
[0022] The heat shielding rate of flash-spun sheets is 20% to 25%.
[0023] The heat shielding rate of flash-spun sheets is 25% to 30%.
[0024] A flash-spun sheet with high heat shielding, wherein the heat shielding rate attenuation rate △S of the flash-spun sheet is 5% to 15%; Where: △S=(S0-S10) / S0*100% S0 is the initial heat shielding rate of the flash-spun sheet; S10 is the final heat shielding rate of the flash-spun sheet; Heat shielding rate test: (1) Place it at 25°C and 65% relative humidity for 24 hours; then measure its shading index and record it as the initial shading index S0; (2) then exposed to a dry heat atmosphere at 90°C for 6 hours, and then cooled for 24 hours at 25°C and 65% relative humidity; (3) Repeat step (2) for nine more treatments, and measure the heat shielding rate of the treated samples according to the national standard GB / T41560-2022, which is recorded as S10.
[0025] The attenuation rate △S of the heat shielding rate of the flash-spun sheet is 5% to 10%.
[0026] The attenuation rate △S of the heat shielding rate of the flash-spun sheet is 10% to 15%.
[0027] A flash-spun sheet with high heat shielding performance, wherein the longitudinal tensile strength (MTS) of the flash-spun sheet is greater than 4.5 KN / m.
[0028] A flash-spun sheet with high heat shielding has a Gurley air permeability resistance of less than 35 seconds. The Gurley air permeability resistance is the time taken to pass 100 ml of gas and is tested according to the national standard GB / T458-2008.
[0029] A high heat shielding flash-spun sheet, the raw material of which further comprises a hybrid material loaded with magnesium oxide.
[0030] The mass fraction of the magnesium oxide-loaded hybrid material in the mixture of the magnesium oxide-loaded hybrid material and polyethylene is 2% to 4%.
[0031] The processing method of the hybrid material loaded with magnesium oxide comprises the following technical steps: (1) Silica particle surface treatment liquid: Adding silica nanoparticles to deionized water for ultrasonic dispersion to obtain a dispersion, then adding polyvinyl alcohol powder to the dispersion, heating and stirring at the same time, controlling the heating temperature to 75°C to 100°C for dissolution and dispersion, after the polyvinyl alcohol solution is dissolved, reacting for 24 hours to 60 hours, then filtering to remove undissolved polyvinyl alcohol to obtain a coating solution, and obtaining a silica particle surface treatment solution; The mass ratio of silicon dioxide nanoparticles to polyvinyl alcohol powder is 1:8 to 1:13; (2) Magnesium-containing precursor dispersion The surface treatment solution of the silicon dioxide particles prepared in step (1) is then added to the magnesium chloride aqueous solution to continue the primary reaction, and the silicon dioxide nanoparticles are loaded on the surface of the silicon dioxide nanoparticles by a chelating reaction with polyvinyl alcohol, and then the pH value of the mixed solution is slowly adjusted to 10.5-12 with an alkali, and a secondary reaction is continued under alkaline conditions to obtain a magnesium-containing precursor dispersion; The primary reaction time is 24 hours to 36 hours, and the reaction temperature is 55°C to 75°C; The alkali may specifically be a 0.2 mol / L sodium hydroxide solution or potassium hydroxide solution; The secondary reaction is carried out under alkaline conditions, and the reaction time is 5 to 10 hours; The internal silicon dioxide is etched, and at the same time, the internal magnesium ions generate magnesium hydroxide precipitation in the alkaline solution, so that etching and precipitation are carried out simultaneously; (3) Hybrid materials loaded with magnesium oxide Finally, the magnesium-containing precursor dispersion in step (2) is separated by centrifugation, and the lower layer of precipitate is taken to obtain a magnesium-containing precursor dispersion; the lower layer of magnesium-containing precursor is aerobically calcined at 180° C. to 200° C. for 15 to 30 minutes, and then rapidly heated to 440° C. to 450° C. within 1 to 5 minutes, and calcined without oxygen for 45 to 60 minutes, and naturally cooled to obtain a hybrid material loaded with magnesium oxide.
[0032] During the calcination process, aerobic calcination is carried out first. Since the polyvinyl alcohol structure is aerobically pre-oxidized and carbonized at 180°C, and magnesium hydroxide is oxidatively decomposed to generate magnesium oxide, and then transferred to high-temperature oxygen-free carbonization to generate magnesium oxide with excellent emission function, the heat shielding performance of the product is improved, and the conventional blending and adding dispersion problems are avoided. In addition, magnesium oxide is generated on the surface of the carbon material to form a relatively stable hybrid material doped with magnesium oxide.
[0033] A processing method for a flash-spun sheet with high heat shielding performance mainly comprises the following technical steps: dissolving a spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding the spinning solution to obtain a flash-spun sheet.
[0034] The spinning raw material is polyethylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 2% to 4%.
[0035] The mass fraction of spinning raw materials in the spinning solution is 6% to 18%.
[0036] The temperature of flash spinning is 180℃~230℃.
[0037] The temperature of hot pressing is 100°C to 115°C.
[0038] The spinning solvents are aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, fluorocarbons and the like. The main solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0039] This application also provides another technical solution: A processing method for a high heat-shielding polypropylene flash-spun sheet mainly comprises the following technical steps: dissolving a spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0040] The spinning raw material is a hybrid material of polypropylene and magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polypropylene) is 2% to 4%.
[0041] The mass fraction of spinning raw materials in the spinning solution is 6% to 18%.
[0042] The temperature of flash spinning is 180℃~230℃.
[0043] The temperature of hot pressing is 100°C to 115°C.
[0044] Compared with the prior art, the present invention has the following positive effects: The present invention provides a method for preparing a hybrid material loaded with magnesium oxide, and finds that adding a certain amount of the hybrid material loaded with magnesium oxide into a spinning raw material can significantly improve the heat shielding performance of the flash-spun sheet obtained, thereby expanding the application depth of the flash-spun sheet. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with specific implementation methods.
[0046] Example 1 The present embodiment provides a high heat shielding flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0047] The spinning raw material is polyethylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 2%.
[0048] The processing method of the hybrid material loaded with magnesium oxide comprises the following technical steps: (1) Silica particle surface treatment liquid: Adding silica nanoparticles to deionized water for ultrasonic dispersion to obtain a dispersion, then adding polyvinyl alcohol powder to the dispersion, heating and stirring at the same time, controlling the heating temperature to 75°C to 100°C for dissolution and dispersion, after the polyvinyl alcohol solution is dissolved, reacting for 24 hours to 60 hours, then filtering to remove undissolved polyvinyl alcohol to obtain a coating solution, and obtaining a silica particle surface treatment solution; The mass ratio of silica nanoparticles to polyvinyl alcohol powder was 1:8; (2) Magnesium-containing precursor dispersion The surface treatment solution of the silicon dioxide particles prepared in step (1) is then added to the magnesium chloride aqueous solution to continue the primary reaction, and the silicon dioxide nanoparticles are loaded on the surface of the silicon dioxide nanoparticles by a chelating reaction with polyvinyl alcohol, and then the pH value of the mixed solution is slowly adjusted to 10.5-12 with an alkali, and a secondary reaction is continued under alkaline conditions to obtain a magnesium-containing precursor dispersion; The primary reaction time is 24 hours, and the reaction temperature is 55°C to 75°C; The alkali may specifically be a 0.2 mol / L sodium hydroxide solution or potassium hydroxide solution; The secondary reaction was carried out under alkaline conditions with a reaction time of 5 hours; The internal silicon dioxide is etched, and at the same time, the internal magnesium ions generate magnesium hydroxide precipitation in the alkaline solution, so that etching and precipitation are carried out simultaneously; (3) Hybrid materials loaded with magnesium oxide Finally, the magnesium-containing precursor dispersion in step (2) is separated by centrifugation, and the lower layer of precipitate is taken to obtain a magnesium-containing precursor dispersion; the lower layer of magnesium-containing precursor is aerobically calcined at 180° C. to 200° C. for 15 to 30 minutes, and then rapidly heated to 440° C. to 450° C. within 1 to 5 minutes, and calcined without oxygen for 45 to 60 minutes, and naturally cooled to obtain a hybrid material loaded with magnesium oxide.
[0049] The mass fraction of spinning raw materials in the spinning solution is 7%.
[0050] The flash spinning temperature was 210°C.
[0051] The temperature of hot pressing was 100°C.
[0052] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0053] The test results of this embodiment are shown in Table 1.
[0054] Example 2 The present embodiment provides a high heat shielding flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0055] The spinning raw material is polyethylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 3%.
[0056] The processing method of the hybrid material loaded with magnesium oxide comprises the following technical steps: (1) Silica particle surface treatment liquid: Adding silica nanoparticles to deionized water for ultrasonic dispersion to obtain a dispersion, then adding polyvinyl alcohol powder to the dispersion, heating and stirring at the same time, controlling the heating temperature to 75°C to 100°C for dissolution and dispersion, after the polyvinyl alcohol solution is dissolved, reacting for 24 hours to 60 hours, then filtering to remove undissolved polyvinyl alcohol to obtain a coating solution, and obtaining a silica particle surface treatment solution; The mass ratio of silica nanoparticles to polyvinyl alcohol powder was 1:10; (2) Magnesium-containing precursor dispersion The surface treatment solution of the silicon dioxide particles prepared in step (1) is then added to the magnesium chloride aqueous solution to continue the primary reaction, and the silicon dioxide nanoparticles are loaded on the surface of the silicon dioxide nanoparticles by a chelating reaction with polyvinyl alcohol, and then the pH value of the mixed solution is slowly adjusted to 10.5-12 with an alkali, and a secondary reaction is continued under alkaline conditions to obtain a magnesium-containing precursor dispersion; The primary reaction time is 30 hours, and the reaction temperature is 55°C to 75°C; The alkali may specifically be a 0.2 mol / L sodium hydroxide solution or potassium hydroxide solution; The secondary reaction was carried out under alkaline conditions with a reaction time of 7 hours; The internal silicon dioxide is etched, and at the same time, the internal magnesium ions generate magnesium hydroxide precipitation in the alkaline solution, so that etching and precipitation are carried out simultaneously; (3) Hybrid materials loaded with magnesium oxide Finally, the magnesium-containing precursor dispersion in step (2) is separated by centrifugation, and the lower layer of precipitate is taken to obtain a magnesium-containing precursor dispersion; the lower layer of magnesium-containing precursor is aerobically calcined at 180° C. to 200° C. for 15 to 30 minutes, and then rapidly heated to 440° C. to 450° C. within 1 to 5 minutes, and calcined without oxygen for 45 to 60 minutes, and naturally cooled to obtain a hybrid material loaded with magnesium oxide.
[0057] The mass fraction of spinning raw materials in the spinning solution is 10%.
[0058] The flash spinning temperature was 220°C.
[0059] The temperature of hot pressing was 110°C.
[0060] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0061] The test results of this embodiment are shown in Table 1.
[0062] Example 3 The present embodiment provides a high heat shielding flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0063] The spinning raw material is polyethylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 4%.
[0064] The processing method of the hybrid material loaded with magnesium oxide comprises the following technical steps: (1) Silica particle surface treatment liquid: Adding silica nanoparticles to deionized water for ultrasonic dispersion to obtain a dispersion, then adding polyvinyl alcohol powder to the dispersion, heating and stirring at the same time, controlling the heating temperature to 75°C to 100°C for dissolution and dispersion, after the polyvinyl alcohol solution is dissolved, reacting for 24 hours to 60 hours, then filtering to remove undissolved polyvinyl alcohol to obtain a coating solution, and obtaining a silica particle surface treatment solution; The mass ratio of silica nanoparticles to polyvinyl alcohol powder was 1:13; (2) Magnesium-containing precursor dispersion The surface treatment solution of the silicon dioxide particles prepared in step (1) is then added to the magnesium chloride aqueous solution to continue the primary reaction, and the silicon dioxide nanoparticles are loaded on the surface of the silicon dioxide nanoparticles by a chelating reaction with polyvinyl alcohol, and then the pH value of the mixed solution is slowly adjusted to 10.5-12 with an alkali, and a secondary reaction is continued under alkaline conditions to obtain a magnesium-containing precursor dispersion; The primary reaction time is 36 hours, and the reaction temperature is 55°C to 75°C; The alkali may specifically be a 0.2 mol / L sodium hydroxide solution or potassium hydroxide solution; The secondary reaction was carried out under alkaline conditions with a reaction time of 10 hours; The internal silicon dioxide is etched, and at the same time, the internal magnesium ions generate magnesium hydroxide precipitation in the alkaline solution, so that etching and precipitation are carried out simultaneously; (3) Hybrid materials loaded with magnesium oxide Finally, the magnesium-containing precursor dispersion in step (2) is separated by centrifugation, and the lower layer of precipitate is taken to obtain a magnesium-containing precursor dispersion; the lower layer of magnesium-containing precursor is aerobically calcined at 180° C. to 200° C. for 15 to 30 minutes, and then rapidly heated to 440° C. to 450° C. within 1 to 5 minutes, and calcined without oxygen for 45 to 60 minutes, and naturally cooled to obtain a hybrid material loaded with magnesium oxide.
[0065] The mass fraction of spinning raw materials in the spinning solution is 14%.
[0066] The flash spinning temperature was 230°C.
[0067] The temperature of hot pressing was 115°C.
[0068] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0069] The test results of this embodiment are shown in Table 1.
[0070] Example 4 The present embodiment provides a high heat shielding flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0071] The spinning raw material is polypropylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 2%.
[0072] The preparation method of the hybrid material loaded with magnesium oxide is the same as that in Example 1.
[0073] The mass fraction of spinning raw materials in the spinning solution is 10%.
[0074] The flash spinning temperature was 215°C.
[0075] The temperature of hot pressing was 110°C.
[0076] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0077] The test results of this embodiment are shown in Table 1.
[0078] Example 5 The present embodiment provides a high heat shielding flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0079] The spinning raw material is polypropylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 3%.
[0080] The preparation method of the hybrid material loaded with magnesium oxide is the same as that in Example 2.
[0081] The mass fraction of spinning raw materials in the spinning solution is 12%.
[0082] The flash spinning temperature was 210°C.
[0083] The temperature of hot pressing was 112°C.
[0084] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0085] The test results of this embodiment are shown in Table 1.
[0086] Example 6 The present embodiment provides a high heat shielding flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0087] The spinning raw material is polypropylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 4%.
[0088] The preparation method of the hybrid material loaded with magnesium oxide is the same as that in Example 3.
[0089] The mass fraction of spinning raw materials in the spinning solution is 15%.
[0090] The flash spinning temperature was 225°C.
[0091] The temperature of hot pressing was 114°C.
[0092] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0093] The test results of this embodiment are shown in Table 1.
[0094] Comparative Example 1 This comparative example provides a method for processing a flash-spun sheet, which mainly comprises the following technical steps: dissolving a spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0095] The spinning material is polyethylene; The mass fraction of spinning raw materials in the spinning solution is 10%.
[0096] The flash spinning temperature was 220°C.
[0097] The temperature of hot pressing was 110°C.
[0098] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0099] The test results of this comparative example are shown in Table 1.
[0100] Comparative Example 2 This comparative example provides a flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving a spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0101] The spinning raw material is polyethylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 0.5%.
[0102] The processing method of the hybrid material loaded with magnesium oxide is the same as that in Example 2.
[0103] The mass fraction of spinning raw materials in the spinning solution is 10%.
[0104] The flash spinning temperature was 220°C.
[0105] The temperature of hot pressing was 110°C.
[0106] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0107] The test results of this embodiment are shown in Table 1.
[0108] Comparative Example 3 This comparative example provides a flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving a spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0109] The spinning raw material is polyethylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 1%.
[0110] The processing method of the hybrid material loaded with magnesium oxide is the same as that in Example 2.
[0111] The mass fraction of spinning raw materials in the spinning solution is 10%.
[0112] The flash spinning temperature was 220°C.
[0113] The temperature of hot pressing was 110°C.
[0114] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0115] The test results of this embodiment are shown in Table 1.
[0116] Comparative Example 4 This comparative example provides a flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving a spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0117] The spinning raw material is polyethylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 5%.
[0118] The processing method of the hybrid material loaded with magnesium oxide is the same as that in Example 2.
[0119] The mass fraction of spinning raw materials in the spinning solution is 10%.
[0120] The flash spinning temperature was 220°C.
[0121] The temperature of hot pressing was 110°C.
[0122] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0123] The test results of this embodiment are shown in Table 1.
[0124] Comparative Example 5 This comparative example provides a flash-spun sheet and a processing method thereof, which mainly comprises the following technical steps: dissolving a spinning raw material in a spinning solvent to obtain a spinning solution, then flash-spinning the spinning solution, and then hot-pressing and winding to obtain a flash-spun sheet.
[0125] The spinning raw material is polyethylene and a hybrid material loaded with magnesium oxide; the mass fraction of the hybrid material loaded with magnesium oxide in the spinning raw material (a mixture of the hybrid material loaded with magnesium oxide and polyethylene) is 7%.
[0126] The processing method of the hybrid material loaded with magnesium oxide is the same as that in Example 2.
[0127] The mass fraction of spinning raw materials in the spinning solution is 10%.
[0128] The flash spinning temperature was 220°C.
[0129] The temperature of hot pressing was 110°C.
[0130] The spinning solvents are trichlorofluoromethane, dichloromethane and 1,1-difluoroethane, and the mass ratio of the three is 4:5:1.
[0131] The test results of this embodiment are shown in Table 1.
[0132] Table 1 Performance test data table of this application S0 (%) △S(%) MTS (KN / m) Geller air permeability resistance (s) Example 1 18 13 4.76 11 Example 2 25 10 5.79 20 Example 3 28 8 6.34 35 Example 4 20 14 6.16 25 Example 5 24 9 8.21 30 Example 6 29 7 10.51 34 Comparative Example 1 7.3 25.2 3.63 5 Comparative Example 2 10.5 19.3 4.24 10 Comparative Example 3 13.2 16.6 4.41 12 Comparative Example 4 29.1 8.4 5.89 65 Comparative Example 5 30.5 7.9 6.01 72 Analysis of results: By comparing the above data, it can be seen that after adding the hybrid material loaded with magnesium oxide prepared in the present application, the obtained flash-spun sheet has obvious improvements in heat shielding performance and heat shielding rate attenuation rate, achieving the expected purpose of the present invention.
[0133] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A flash-spun sheet with high heat shielding, characterized in that: The raw material of the flash spun sheet includes polyethylene, and the thickness of the flash spun sheet is 0.1 mm to 0.5 mm; The heat shielding rate of flash-spun sheets is 15% to 30%.
2. A high heat shielding flash-spun sheet as claimed in claim 1, characterized in that: The thickness of the flash-spun sheet is 0.15 mm to 0.3 mm.
3. A high heat shielding flash-spun sheet as claimed in claim 1, characterized in that: The weight of flash spun sheets is greater than 30g / m 2 .
4. A flash-spun sheet with high heat shielding properties as claimed in claim 1, characterized in that: The weight of flash spun sheets is less than 120g / m 2 .
5. A flash-spun sheet with high heat shielding properties as claimed in claim 1, characterized in that: The heat shielding rate of flash-spun sheets is 15% to 20%.
6. A flash-spun sheet with high heat shielding properties as claimed in claim 1, characterized in that: The heat shielding rate of flash-spun sheets is 20% to 25%.
7. A flash-spun sheet with high heat shielding properties as claimed in claim 1, characterized in that: The heat shielding rate of flash-spun sheets is 25% to 30%.
8. A flash-spun sheet with high heat shielding properties as claimed in claim 1, characterized in that: The decay rate △S of the heat shielding rate of the flash-spun sheet is 5% to 15%; Where: △S = (S0-S 10 ) / S0*100%; S0 is the initial heat shielding rate of the flash-spun sheet; S 10 is the final heat shielding rate of the flash-spun sheet; Heat shielding rate test: (1) Place it at 25°C and 65% relative humidity for 24 hours; then measure its shading index and record it as the initial shading index S0; (2) then exposed to a dry heat atmosphere at 90°C for 6 hours, and then cooled for 24 hours at 25°C and 65% relative humidity; (3) Repeat step (2) for another nine treatments, and measure the heat shielding rate of the treated samples according to the national standard GB / T 41560-2022, which is recorded as S 10 .
9. A flash-spun sheet with high heat shielding properties as claimed in claim 8, characterized in that: The attenuation rate △S of the heat shielding rate of the flash-spun sheet is 5% to 10%.
10. A flash-spun sheet with high heat shielding properties as claimed in claim 8, characterized in that: The attenuation rate △S of the heat shielding rate of the flash-spun sheet is 10% to 15%.
11. A flash-spun sheet with high heat shielding properties as claimed in claim 1, characterized in that: The longitudinal tensile strength MTS of the flash-spun sheet is greater than 4.5 KN / m.
12. A flash-spun sheet with high heat shielding properties as claimed in claim 1, characterized in that: The Gurley air permeability resistance of the flash-spun sheet is less than 35s.
Citation Information
Patent Citations
Polyethylene non-woven fabric and application thereof
CN114622341A
Multifunctional polymer non-woven fabric and fabric thereof
CN114687069A
Light and thin flash polymer non-woven fabric
CN114908478A
Flash fabric and application thereof
CN114990712A
Flash-spun sheet material
EP1213374A2